Mechanisms for the Generation of Two Quadruplications Associated with Split‐Hand Malformation. Issue 2 (2nd December 2015) - Gu, Shen; Posey, Jennifer E.; Yuan, Bo; Carvalho, Claudia M.B.; Luk, H.M.; Erikson, Kelly; Lo, Ivan F.M.; Leung, Gordon K.C.; Pickering, Curtis R.; Chung, Brian H.Y.; Lupski, James R.
Abstract : Proposed three‐step process. Step 1, a duplication‐normal‐duplication rearrangement pattern is formed from the reference allele via a replication‐based mechanism(s) generating Alu‐Alu mediated Jct1 and Jct2. Step 2, by utilizing the duplicated Region 2 as potential LCRs, Region 1 and Region 2 are further amplified through intrachromosomal (interchromatidal) NAHR, resulting in the two triplications observed in the maternal grandmother. Step 3, another intergenerational intrachromosomal NAHR results in the two quadruplications pattern in the mother and her two offspring. ABSTRACT: Germline copy‐number variants (CNVs) involving quadruplications are rare and the mechanisms generating them are largely unknown. Previously, we reported a 20‐week gestation fetus with split‐hand malformation; clinical microarray detected two maternally inherited triplications separated by a copy‐number neutral region at 17p13.3, involving BHLHA9 and part of YWHAE . Here, we describe an 18‐month‐old male sibling of the previously described fetus with split‐hand malformation. Custom high‐density microarray and digital droplet PCR revealed the copy‐number gains were actually quadruplications in the mother, the fetus, and her later born son. This quadruplication‐normal‐quadruplication pattern was shown to be expanded from the triplication‐normal‐triplication CNV at the same loci in the maternal grandmother. We mapped two breakpoint junctions and demonstrated that both are mediated by Alu repetitive elements and identical in these four individuals. We propose a three‐step process combining Alu ‐mediated replicative‐repair‐based mechanism(s) and intergenerational, intrachromosomal nonallelic homologous recombination to generate the quadruplications in this family.